Streamlining the broiler chicken supply chain in practice via mixed-integer programming (2019)
In the poultry industry, the meat market requires a careful coordination of the broiler chicken supply chain which is comprised of hatcheries, farms, slaughtering houses, wholesale, and retail vendors. Aside from the inherent challenges of coordinating a supply chain, livestock systems face additional difficult tasks. Lack of coordination within the poultry chain could lead to a production plan that fails the biosecurity standards required for meat for human consumption. To streamline the supply chain, we propose a mixed-integer linear programming model that supports production planning and scheduling decisions in the farm and slaughtering operations at a broiler chicken production facility. We present the results of a case study in Santa Marta (Colombia) where we reached major savings while meeting stringent technical, operational, and biosecurity constraints.